Reconsidering digital strategies for recruiting and organising young emerging teachers in chosen teachers' unions in South Africa - Fakude, Xolani; Matsepe, David; Maluleke, Mugwena (Penerbit Universiti Kebangsaan Malaysia, 2024)
The International Labour Organisation (ILO) reports that, in most of its member countries, the percentage of employed individuals who are members of trade unions has decreased significantly over the past few decades, with less than 20 percent. Some of the studies done on this subject unequivocally acknowledge that low membership turnover and dwindling trade union densities are caused by the incapacity to mobilize, organize, and serve members. In order to determine the most effective and efficient way to use these integrated digital strategies, this research investigates types of digital modes for organising, mobilising, and retaining new coming educators. Data were gathered through interviews with ten SADTU organisers and ten students from particular South. African universities, using the qualitative method. The data was analysed using a grounded (thematic) approach. The study's overall findings shows that digital technologies play a significant role in luring newer generations of trade union members. The findings of this study directly influenced the creation of more precise and efficient digital strategies for recruiting and organizing young emerging teachers, leading to an overall enhancement in the recruitment and retention of talent within the education sector.